Evaluation of tooth root surface area using a three-dimensional scanning technique and cone beam computed tomographic reconstruction in vitro. (December 2017) - Wang, Tong; Pei, Xibo; Luo, Feng; Jia, Lingling; Qin, Han; Cheng, Xinting; Xue, Yiyuan; Wang, Jian; Wan, Qianbing
Highlights: PVA-SA-SDBS-MWCNTs mixture could be used as membrane material to measure RSA. 3D scanning and CBCT reconstruction could be an accurate way to measure the RSA. The RSA were not significantly different when measured among all three methods. Abstract: Objective: To study the feasibility of measuring root surface area (RSA) by 3D scanning technique and cone beam computed tomography (CBCT) reconstruction in vitro. Design: Twenty extracted teeth (10 single-rooted teeth and 10 multi-rooted teeth) were collected in this study. The RSA of the extracted teeth was measured by the membrane technique, 3D scanning technique, and CBCT reconstruction. A standard part was also designed to check the accuracy of each method. All statistical analyses were performed using the SPSS software. Results: According to the results of one-way ANOVA, there was no significant difference among the values of RSA measured by the three techniques ( p > 0.05). The results of Wilcoxon matched-pairs signed-rank test further demonstrated that there was no significant difference among the values of RSA in both single- and multi-rooted teeth measured by the three techniques ( p > 0.05). Conclusions: The membrane technique, the 3D scanning technique, and CBCT reconstruction are novel reliable techniques for measuring the RSA in both single- and multi-rooted teeth, which will provide wide clinical applications in the future.